O teorema dos números primos - Vieira, Márcia Oliveira (2023)
The objective of this work is to present prime numbers and show a relationship between the prime counting function, π(x), and the natural logarithm function, log(x). Initially, we will make a brief historical overview. Next, we will bring some important concepts about prime numbers and about some elements of Complex Analysis. Finally, we will study the Riemann Zeta function and bring the demonstration of the Prime Number Theorem, tracing a connection between the Riemann Zeta function and the π(x) function.